The orphan G protein‐coupled receptor GPR149 is a negative regulator of myelination and remyelination. Issue 10 (27th June 2022) - Suo, Na; He, Bingqing; Cui, Shihao; Yang, Ying; Wang, Min; Yuan, Qianting; Xie, Xin
Abstract: Myelin sheath, formed by oligodendrocytes (OLs) in the central nervous system (CNS) and Schwann cells in periphery, plays a critical role in supporting neuronal functions. OLs, differentiated from oligodendrocyte precursor cells (OPCs), are important for myelination during development and myelin repair in CNS demyelinating disease. To identify mechanisms of myelin development and remyelination after myelin damage is of great clinical interest. Here we show that the orphan G protein‐coupled receptor GPR149, enriched in OPCs, negatively regulate OPC to OL differentiation, myelination, as well as remyelination. The expression of GPR149 is downregulated during OPCs differentiation into OLs. GPR149 deficiency does not affect the number of OPCs, but promotes OPC to OL differentiation which results in earlier development of myelin. In cuprizone‐induced demyelination model, GPR149 deficiency significantly enhances myelin regeneration. Further study indicates that GPR149 may regulate OL differentiation and myelin formation via MAPK/ERK pathway. Our study suggests that deleting or blocking GPR149 might be an intriguing way to promote myelin repair in demyelinating diseases. Main Points: GPR149, enriched in OPCs, negatively regulates myelin formation via ERK activation. GPR149 deletion promotes OPC to oligodendrocyte differentiation which results in earlier development of myelin and enhanced myelin recovery in demyelination model.